PENGARUH KUALITAS PELAYANAN, KEWAJIBAN MORAL DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK HOTEL DALAM MEMBAYAR PAJAK HOTEL (Studi KasusPada Wajib Pajak Hotel di Kota pekanbaru) - Rahayu, Puji; Satriawan, Raja Adri; -, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of quality of service , moral obligation and tax penalties on tax compliance in paying hotel tax. This study was performed on taxpayers listed in DISPENDA of Pekanbaru city. The total of sample in this study were as many as 121 registered taxpayers.analysis method used in this study was moderate regression analysis using SPSS version 17.0.The results showed that the quality of service, moral obligation, and tax penalties effect the compliance hotel tax. The results showed that the quality of service , quality of service , moral obligation and tax penalties effect on tax compliance in these pay hotel tax . the result that the quality of service . tcount ( 2.596 ) > t table ( 2.008 ) andsignificance ( 0.012 ) < 0.05 . Moral obligation t ( 2.950 ) > table ( 2.008 ) and significance was ( 0.005 ) < 0.05 . Tax penalties known to show t count( 2.705 ) > t table ( 2.008 ) and significance was ( 0.009 ) < 0.05.R2 value that is equal to 56.1 % . While the remaining 43.9 % is influenced by other variables not included in this regression modelKeywords: qulity of service, moral obligation, tax penalties, compliance